Implementación del sistema de gestión de la seguridad y salud en el trabajo para la empresa Autopista140 Ltda. De acuerdo con el decreto 1072 de 2015 capítulo 6, el decreto 052 de 2017 y la resolución 1111 de 2017 (2019)
In the development of the degree work, the different activities aimed at fulfilling the objectives presented in the preliminary project were carried out. This was established under the guidelines of Decree 1072 of 2015 as the main guide, together with Resolution 1111 of 2017, which gives the parameters to follow from the diagnosis, until the internal audit; For the following chapters, the guidelines established in Resolution 0312 of 2019 in its chapter 1 are taken as a fundamental parameter. The project began with a diagnosis, which defined the situation presented by the company in terms of compliance with the minimum standards present in Resolution 1111 of 2017, after which the legal matrix was developed, which allowed identifying the laws, regulations, and decrees, which the company must comply with for its operation, after which the hazard identification and risk mitigation matrix was developed in which risks and safety risks were studied and evaluated.